Parameterization and Remote Sensing Retrieval of Land Surface Processes in the Gurbantunggut Desert, China - Wei Li; Jiacheng Gao; Ali Mamtimin; Yongqiang Liu; Yu Wang; Meiqi Song; Cong Wen; Ailiyaer Aihaiti; Fan Yang; Wen Huo; Chenglong Zhou; Wenbiao Wang; et al. (Remote Sensing, 2023)
The exchange of energy between the land surface and atmosphere is dependent upon crucial parameters, including surface roughness, emissivity, bulk transfer coefficients for momentum (CD) and heat (CH). These parameters are calculated through site observation data and remote sensing data. The following conclusions are drawn: (1) the aerodynamic roughness of the Gurbantunggut Desert measures 1.1 × 10−2 m, which is influenced by the varying conditions of the underlying surface. The roughness decreases as wind speed increases and is seen to be directly proportional to the growth of vegetation. From April to June, the aerodynamic roughness increases with increasing vegetation cover, but begins to gradually decrease after July. Spatially, the middle regions show higher roughness values than the eastern and western areas. In the central part of the desert, the roughness is between 2.37 × 10−2 m and 2.46 × 10−2 m from April to November. The northwest and northeast regions measure 1.41 × 10−2 m–2.04 × 10−2 m and 1.53 × 10−2 m–2.39 × 10−2 m, respectively. (2) The surface emissivity is 0.93, and it varies depending on the snow and vegetation present in the underlying area. (3) CD and CH exhibit an inverse relationship with wind speed. When wind speed falls below 6 m/s, the CD declines rapidly as wind speed increases. In contrast, once wind speed surpasses 6 m/s, the propensity for the CD to decrease with increasing wind speed slows down and approaches stability.